TP53 Mutations in Acute Myeloid Leukemia: Still a Daunting Challenge? - Molica, Matteo; Mazzone, Carla; Niscola, Pasquale; de Fabritiis, Paolo (Frontiers in Oncology, 2021)
TP53 is a key tumor suppressor gene with protean functions related to maintenance of genomic stability, including regulation of cellular senescence, apoptosis, metabolism, and DNA repair. The vast majority of cases of de novo acute myeloid leukemia (AML) have unaltered TP53 alleles. TP53 mutations are, however, more common in AML with increased genomic instability, such as therapy‐related (t-AML) or AML with myelodysplasia-related changes. Of note, TP53 mutations are associated with complex cytogenetic abnormalities, advanced age, chemoresistance, and poor survival. Recent breakthroughs in AML research and the development of targeted drugs directed at specific mutations have led to an explosion of novel treatments with different mechanisms. However, optimal treatment strategy for patients harboring TP53 mutations remains a critical area of unmet need. In this review, we focus on the incidence and clinical significance of TP53 mutations in de novo and t-AML. The influence of these alterations on response and clinical outcomes as well as the current and future therapeutic perspectives for this hardly treatable setting are discussed.